Contemporary outcomes of composite aortic root replacement in elderly patients. (22nd November 2019) - Okamura, Homare; Arakawa, Mamoru; Kimura, Naoyuki; Yuri, Koichi; Yamaguchi, Atsushi
Abstract: : OBJECTIVES: We investigated the clinical and haemodynamic outcomes in elderly patients undergoing composite aortic root replacement. METHODS: Between 2005 and 2017, 135 patients underwent aortic root surgery at our hospital. Of these 135 patients, 47 patients aged ≥65 years were included in this study. Pathologies included aneurysms in 31, chronic aortic dissection in 6, acute aortic dissection in 4 and other causes in 6 patients. A bioprosthesis was used in 27 and a mechanical valve in 20 patients. The mean age was 71.0 ± 4.3 years. The mean follow-up period was 61 ± 35 months. Follow-up echocardiographic data (average 48 months after surgery) were collected in 35 patients (74%). RESULTS: The in-hospital mortality rate was 2.1% (1 patient). Seven late deaths occurred during follow-up. The 1-, 5- and 8-year overall survival was 93.6%, 82.9% and 82.9%, respectively. Infective endocarditis, Marfan syndrome and diabetes were independent predictors of poorer survival. During the follow-up, thromboembolism occurred in 1 patient, major bleeding events in 5 patients, or proximal reoperation for prosthetic valve endocarditis in 1 patient. The type of valve, mechanical or biological valve, did not affect late mortality and morbidity. Follow-up echocardiography revealed significantly improved left ventricular ejection fraction compared with that at discharge. CONCLUSIONS: Composite aortic root replacement provided satisfactory midterm outcomes in patients aged ≥65 years. Further studies with a longer follow-up are warranted to evaluate late valve-related events.